ANALYTIC APPROXIMATE SOLUTIONS FOR FLUID-FLOW IN THE PRESENCE OF HEAT AND MASS TRANSFER - Kilicman, Adem; Khan, Yasir; Akgul, Ali; Faraz, Naeem; Akgul, Esra Karatas; İnç, Mustafa (Vinca Inst Nuclear Sci, 2018)
This paper outlines a comprehensive study of the fluid-flow in the presence of heat and mass transfer. The governing non-linear ODE are solved by means of the homotopy perturbation method. A comparison of the present solution is also made with the existing solution and excellent agreement is observed. The implementation of homotopy perturbation method proved to be extremely effective and highly suitable. The solution procedure explicitly elucidates the remarkable accuracy of the proposed algorithm.
Keywords: homotopy perturbation method; heat and mass transfer; fluid-flow